The spectral analysis of the conception of administratively-legal mechanism of securing the implementation of subjective electoral right of the subject of electoral process which connected with local elections - Розум, Ігор Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
Within the limits of conducting the scientifical research author has made system analysis of administratively-legal mechanism of securing the implementation of subjective electoral right of the subject of electoralprocess which connected with local elections, formulated its definition and legal forms.